2010
DOI: 10.1002/mrd.21164
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B activity is related to the quality of bovine cumulus oocyte complexes and its inhibition can improve their developmental competence

Abstract: Recently, the quantity of cathepsin transcripts in cumulus cells was found to be associated with low-developmental competence of bovine oocytes. In the present study, we investigated (1) the relation between cathepsin B activity and the quality of in vitro-matured cumulus-oocyte complexes (IVM COCs) and denuded oocytes and (2) the effect of a cathepsin B inhibitor (E-64) on embryo development and quality. The activity of cathepsin B was evaluated in IVM COCs and denuded oocytes. After maturation of COCs with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 38 publications
3
49
1
1
Order By: Relevance
“…Bettegowda et al (2008) first reported that cumulus cells of low developmental competence oocytes showed higher expression of cathepsin B mRNA than those of high developmental competence oocytes (Bettegowda et al 2008). Moreover, our previous studies clearly showed that cathepsin B activity is inversely correlated with the quality of bovine COCs and embryos by the higher activity and protein expression of cathepsin B in poor-quality in vitro matured oocytes and embryos than in good-quality ones (Balboula et al 2010a(Balboula et al , 2010b. Furthermore, cathepsin B was found to impair the oocyte and embryo developmental competence by possible stimulation of the apoptotic pathway (Balboula et al 2010a(Balboula et al , 2010b.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Bettegowda et al (2008) first reported that cumulus cells of low developmental competence oocytes showed higher expression of cathepsin B mRNA than those of high developmental competence oocytes (Bettegowda et al 2008). Moreover, our previous studies clearly showed that cathepsin B activity is inversely correlated with the quality of bovine COCs and embryos by the higher activity and protein expression of cathepsin B in poor-quality in vitro matured oocytes and embryos than in good-quality ones (Balboula et al 2010a(Balboula et al , 2010b. Furthermore, cathepsin B was found to impair the oocyte and embryo developmental competence by possible stimulation of the apoptotic pathway (Balboula et al 2010a(Balboula et al , 2010b.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, our previous studies clearly showed that cathepsin B activity is inversely correlated with the quality of bovine COCs and embryos by the higher activity and protein expression of cathepsin B in poor-quality in vitro matured oocytes and embryos than in good-quality ones (Balboula et al 2010a(Balboula et al , 2010b. Furthermore, cathepsin B was found to impair the oocyte and embryo developmental competence by possible stimulation of the apoptotic pathway (Balboula et al 2010a(Balboula et al , 2010b. In this study, the significant decrease in TUNEL apoptosis in heat-shocked bovine COCs after the addition of cathepsin B inhibitor (E-64) to the IVM medium clearly showed that cathepsin B has one of the key roles in inducing apoptosis during heat shock of bovine COCs.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, expression of cathepsin B is higher in poor quality bovine oocytes as compared to good-quality ones [22]. In this regard, Balboula et al showed that addition of 1 μM E-64 during in vitro maturation (IVM), improves quality of COCs and their developmental competency.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Min et al (2014) reported that treatment during IVC with E-64 (0.1 and 0.5 μM) significantly improves developmental rates without any noticeable effect on cleavage rate [24]. Unlike the former study which assessed role of cathepsin B inhibition during IVM, other research groups showed that addition of E-64 during in vitro culture (IVC) also improves rate and quality of derived blastocysts [7, 22, 24, 34]. Both these studies concluded that addition of E-64 to IVC medium has no effect on early cleavage rates.…”
Section: Discussionmentioning
confidence: 99%